2004
DOI: 10.1111/j.1095-8339.2004.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

New Silurian cooksonias from dolostones of north-eastern North America

Abstract: New specimens of Cooksonia and Hostinella are described from the Bertie Group of Ontario and New York State, which is dated by faunas as latest Silurian (P ídolí). The rare plant fossils are unusual in that they are preserved in fine-grained, slightly argillaceous dolostones ('waterlime') rather than clastic rocks. At least two species of Cooksonia are present, one with ± globular sporangial morphology close to C. hemisphaerica Lang. Those with ellipsoidal/ discoidal sporangia are compared with C. pertoni Lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…In parts of the central Appalachians, there are small organic fragments scattered throughout the carbonatedominated sequences that lie between the Bloomsburg and the Bertie Waterlime, but these remain undocumented. None of the specimens of Cooksonia described by Banks (1973) or Edwards et al (2004) possesses convincing evidence of tracheids. However, several specimens of Cooksonia illustrated by Edwards et al (2004) clearly show coalified central strands.…”
Section: Silurian Thalloid Floras In the Appalachian Basinmentioning
confidence: 94%
See 2 more Smart Citations
“…In parts of the central Appalachians, there are small organic fragments scattered throughout the carbonatedominated sequences that lie between the Bloomsburg and the Bertie Waterlime, but these remain undocumented. None of the specimens of Cooksonia described by Banks (1973) or Edwards et al (2004) possesses convincing evidence of tracheids. However, several specimens of Cooksonia illustrated by Edwards et al (2004) clearly show coalified central strands.…”
Section: Silurian Thalloid Floras In the Appalachian Basinmentioning
confidence: 94%
“…None of the specimens of Cooksonia described by Banks (1973) or Edwards et al (2004) possesses convincing evidence of tracheids. However, several specimens of Cooksonia illustrated by Edwards et al (2004) clearly show coalified central strands. Tomescu et al (2009) have demonstrated that the carbon isotopic signatures of all of the Silurian thalloid compressions throughout the central Appalachian Basin are consistent with a terrestrial origin.…”
Section: Silurian Thalloid Floras In the Appalachian Basinmentioning
confidence: 94%
See 1 more Smart Citation
“…Other Silurian (Přidolí Series) evidence includes records from Kazakhstan, Podolia [11] and possibly China [27]. Further corroborating evidence comes from early records of Cooksonia that are probably also within the Lycophytina total group, including several species from the Silurian (Přidolí Series): Cooksonia caledonica (Bolivia, Britain), Cooksonia bohemica (Czech Republic) and Cooksonia cambrensis (Britain) [20,28]. The earliest evidence of the Euphyllophytina total group is Wutubulaka multidichotoma from the Late Silurian (Přidolí Series) of Xinjiang, China [27].…”
Section: Land Colonization: Fossil Evidencementioning
confidence: 95%
“…Although OʼConnell's () early deltaic interpretation has since been widely contested, the presence of terrestrial plants ( Cooksonia ; Edwards et al . ) and early fish (Burrow & Rudkin ) in the Williamsville Formation A Member may be indication of a nearby fluviatile source and thus further evidence for reduced salinity levels.…”
Section: Geological Settingmentioning
confidence: 88%